FACTORS ASSOCIATED WITH POST-CESAREAN SECTION WOUND HEALING - Dewi Masitah; Rini Kristiyanti (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Sectio Caesarea (SC) is a surgical procedure to remove a baby from the mother's uterus. SC wound infection is a complication that can increase morbidity and mortality rates. Several factors influence SC wound healing. The purpose of this study was to determine the factors that influence SC wound healing at Bendan Hospital. This study used descriptive analytic design through cross-sectional approach by using chi-square test and logistic regression test. The population of this study were all postpartum mothers from November 17 - December 20, 2023, with a total sampling technique to obtain a sample of 70 respondents. The results of bivariate analysis showed there was a relationship between age (ρ=0.015), personal hygiene (ρ=0.015), anemia status (ρ=0.023), and fulfillment of nutrition (ρ=0.025). There was no association between BMI (ρ=0.579) and wound care knowledge (ρ=0.634). Multivariate analysis showed nutritional fulfillment had a value of ρ=0.042 and OR: 3,862. So the factor that most influences SC wound healing at Bendan Hospital is the fulfillment of nutrition. It is expected that health workers can provide education about nutrition to support SC wound healing to reduce SC wound infection.